Análise da eficiência energética em edificações usando os métodos RTQ-C e INI-C - Andrade, Henrique José Caravita de (2022)
The urban development of the last decades has caused a considerable increase in the energy consumption of buildings, which increased the interest in improving the energy efficiency of buildings justifying the use of the National Energy Conservation Label (ENCE) for commercial, service and public buildings. The method of the Technical Regulation on the Quality of the Energy Efficiency Level of Commercial, Service and Public Buildings (RTQ-C) is used for the labeling process in the construction of new federal public buildings and in the retrofit of existing ones. The Inmetro Normative Instruction for the Energy Efficiency Level of Commercial, Service and Public Buildings (INI-C) aims to replace the RTQ-C method. In this sense, the present research aims to apply and compare the simulation methods for classification in terms of energy efficiency proposed by RTQ-C and INI-C in a building at the Federal University of São Carlos (UFSCar). To this end, the Energy Plus and SketchUP programs were used and the bioclimatic zoning in which the building is inserted, in addition to its constructive characteristics, were considered. The energy efficiency results according to the RTQ-C model classified the building at level "B", however the final classification was "C", because it didn’t meet some of its prerequisites. The INI-C model, on the other hand, classifies the building at level “B” and presents a 33.5% reduction in estimated energy consumption under current operating conditions. In conclusion, the simulation procedures of the INI-C methodology are, in general, simpler to be performed, as they require the creation of a smaller number of models than the RTQ-C methodology. In addition, the INI-C showed greater accuracy in the classification of the building, as it has pre-established parameters for all the variables necessary for the development of the models. However, it can be said that it is easier to obtain a better classification using the INI-C methodology compared to the RTQ-C methodology.